De novo ARF3 variants cause neurodevelopmental disorder with brain abnormality. Issue 1 (4th August 2021) - Sakamoto, Masamune; Sasaki, Kazunori; Sugie, Atsushi; Nitta, Yohei; Kimura, Tetsuaki; Gürsoy, Semra; Cinleti, Tayfun; Iai, Mizue; Sengoku, Toru; Ogata, Kazuhiro; Suzuki, Atsushi; Okamoto, Nobuhiko; et al.
Abstract: An optimal Golgi transport system is important for mammalian cells. The adenosine diphosphate (ADP) ribosylation factors (ARF) are key proteins for regulating cargo sorting at the Golgi network. In this family, ARF3 mainly works at the trans-Golgi network (TGN), and no ARF3 -related phenotypes have yet been described in humans. We here report the clinical and genetic evaluations of two unrelated children with de novo pathogenic variants in the ARF3 gene: c.200A > T (p.Asp67Val) and c.296G > T (p.Arg99Leu). Although the affected individuals presented commonly with developmental delay, epilepsy and brain abnormalities, there were differences in severity, clinical course and brain lesions. In vitro subcellular localization assays revealed that the p.Arg99Leu mutant localized to Golgi apparatus, similar to the wild-type, whereas the p.Asp67Val mutant tended to show a disperse cytosolic pattern together with abnormally dispersed Golgi localization, similar to that observed in a known dominant negative variant (p.Thr31Asn). Pull-down assays revealed that the p.Asp67Val had a loss-of-function effect and the p.Arg99Leu variant had increased binding of the adaptor protein, Golgi-localized, γ-adaptin ear-containing, ARF-binding protein 1 (GGA1), supporting the gain of function. Furthermore, in vivo studies revealed that p.Asp67Val transfection led to lethality in flies. In contrast, flies expressing p.Arg99Leu had abnormal rough eye, as observed in the gain-of-function variant p.Gln71Leu. These data indicate that two ARF3 variants, the possibly loss-of-function p.Asp67Val and the gain-of-function p.Arg99Leu, both impair the Golgi transport system. Therefore, it may not be unreasonable that they showed different clinical features like diffuse brain atrophy (p.Asp67Val) and cerebellar hypoplasia (p.Arg99Leu).